Pain assessment tools for older adults with dementia in long-term care facilities: a systematic review. (December 2016) - Chow, Selina; Chow, Ronald; Lam, Michael; Rowbottom, Leigha; Hollenberg, Drew; Friesen, Erika; Nadalini, Olivia; Lam, Henry; DeAngelis, Carlo; Herrmann, Nathan
Aim: The aim of this review is to document pain assessment tools used primarily for older adults in long-term care facilities and compare self-report and observer-rated tools.Methods: A literature search was conducted in Ovid MEDLINE ®, Embase, Cochrane and PsycINFO. Keywords included 'dementia', 'pain management' and 'managing pain'.Results: Of 1033 references, 23 articles were selected for inclusion. Six tools were self-rated and 18 tools were administered by an observer. 13 studies evaluated the reliability/validity of their scales; four studies compared different scales against each other.Conclusion: Self-report should be the first-line approach when possible, with observational assessment used as a supplementary tool. Reliable observational tools have been shortened, and shown to maintain high reliability/validity, and positive psychometric properties.